PENINGKATAN HASIL BELAJAR SISWA DENGAN PENERAPAN MODEL PEMBELAJARAN GROUP INVESTIGATION BERBASIS LINGKUNGAN SEKOLAH - Ekayanti, Ni Wayan; Setiawati, Gusti Ayu Dewi (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2017)
The purpose of this study is to analyze the improvement of student learning outcomes by using the school environment as a medium of learning with group investigation model. The method used in this research is quasi experiment using One Group Pretest-Posttest Design. The sample of this research is students of class VIIB SMPN 5 Denpasar. The results showed that there were significant differences in learning outcomes (p = 0,000 *) between before and after school-based learning by using group investigation model. So it can be concluded that the model of study group investigation based on school environment as a medium of learning can improve student learning outcomes.